2004
DOI: 10.1109/tps.2004.828806
|View full text |Cite
|
Sign up to set email alerts
|

Low-Noise Microwave Oven Magnetrons With Fast Start-Oscillation by Azimuthally Varying Axial Magnetic Fields

Abstract: A technique has been proven to significantly reduce the noise and to hasten the startup in microwave signals from dc operating oven magnetrons. The technique is based on imposition of an azimuthally varying axial magnetic field in magnetrons. For an -cavity magnetron operating in pi-mode, the optimal number of periods of azimuthal variations in the axial magnetic field is 2. This technique demonstrates the fastest startup and lowest start-oscillation current by prebunching the electrons. Measurements show dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…It is of interest to consider now how different levels of ripple and changing load condition affect the locking performance. Recent work by Neculaes et al [11] has indicated that there is scope for improving the intrinsic noise performance of CW magnetrons. The techniques suggested may well allow systems to be created with a substantially more robust locking performance at the to dB injection level.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to consider now how different levels of ripple and changing load condition affect the locking performance. Recent work by Neculaes et al [11] has indicated that there is scope for improving the intrinsic noise performance of CW magnetrons. The techniques suggested may well allow systems to be created with a substantially more robust locking performance at the to dB injection level.…”
Section: Discussionmentioning
confidence: 99%
“…R ECENT experiments have shown that the sidebands and the close-in noise in a microwave oven magnetron may be eliminated, at the limit of spectrum sensitivity, by the addition of an azimuthally varying axial magnetic field [1], [2]. Noise reduction for 2.45-GHz microwave oven magnetrons is an important issue, as there exists an increasing concern about signal interference for cordless phones and wireless communications systems which also operate in this unlicensed frequency band [3], [4].…”
Section: Rapid Kinematic Bunching and Parametric Instability In A Cromentioning
confidence: 99%
“…Noise reduction for 2.45-GHz microwave oven magnetrons is an important issue, as there exists an increasing concern about signal interference for cordless phones and wireless communications systems which also operate in this unlicensed frequency band [3], [4]. Not only the low noise behavior was observed, but also the startup was found to be substantially hastened when the number of the perturbing magnets equals the number of electron spokes in the operating mode of the magnetron (usually the pi-mode, in which the radio frequency (RF) electric field differs by in neighboring cavities [2], [5]). We call this technique "magnetic priming" and for an -cavity magnetron operating in the pi-mode it consists of imposition of /2 azimuthal magnetic field perturbations.…”
Section: Rapid Kinematic Bunching and Parametric Instability In A Cromentioning
confidence: 99%
See 2 more Smart Citations